1979
DOI: 10.1172/jci109442
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that Increased Circulating 1α,25-Dihydroxyvitamin D is the Probable Cause for Abnormal Calcium Metabolism in Sarcoidosis

Abstract: A B S T R A C T Mean plasma 1,,25-dihydroxyvitamin D [1,,25(OH)2D] was significantly increased and serum parathyroid hormone was suppressed in three patients with sarcoidosis and hypercalcemia. Prednisone lowered the mean plasma 1,,25(OH)2D to normal range and corrected the hypercalcemia. To elucidate the mechanism for the increased sensitivity to vitamin D in this disorder, the effects of orally-administered vitamin D2 were determined in seven normal subjects, four patients with sarcoidosis and normal calcium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
112
1
1

Year Published

1982
1982
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 298 publications
(119 citation statements)
references
References 29 publications
5
112
1
1
Order By: Relevance
“…(7) Fuller Albright published elegant calcium balance studies in 1956 showing a pattern of hypercalcemia and hypercalciuria in sarcoid patients that was consistent with excess vitamin D. (8) Later, in the 1970s, it was shown that 1,25(OH) 2 D levels were elevated in hypercalcemic patients with sarcoidosis. (9,10) However, the source of this 1,25(OH) 2 D was not immediately clear. In 1981, Barbour and colleagues described a patient with renal failure, sarcoidosis-related hypercalcemia, and elevated serum 1,25(OH) 2 D. When the patient underwent bilateral nephrectomy in anticipation of a kidney transplant, his 1,25(OH) 2 D level remained elevated, and he continued to require steroids to maintain the serum calcium level within the normal range.…”
Section: Discussionmentioning
confidence: 99%
“…(7) Fuller Albright published elegant calcium balance studies in 1956 showing a pattern of hypercalcemia and hypercalciuria in sarcoid patients that was consistent with excess vitamin D. (8) Later, in the 1970s, it was shown that 1,25(OH) 2 D levels were elevated in hypercalcemic patients with sarcoidosis. (9,10) However, the source of this 1,25(OH) 2 D was not immediately clear. In 1981, Barbour and colleagues described a patient with renal failure, sarcoidosis-related hypercalcemia, and elevated serum 1,25(OH) 2 D. When the patient underwent bilateral nephrectomy in anticipation of a kidney transplant, his 1,25(OH) 2 D level remained elevated, and he continued to require steroids to maintain the serum calcium level within the normal range.…”
Section: Discussionmentioning
confidence: 99%
“…Extrarenal production of 1,25(OH)2Dis the main mechanism for development of hypercalcemia in sarcoidosis (6,7). In certain granulomatousdiseases such as sarcoidosis, various cytokines are knownto induce 25(OH)D-loc-hydroxylase in macrophages, in which serum ACE,a marker for macrophage activation, is often elevated (8,9). Therefore, hypercalcemic sarcoid patients show abnormally high 1,25(OH)2D levels in spite of having undetectable levels of intact PTH (7).…”
Section: Discussionmentioning
confidence: 99%
“…25-hydroxyvitamin D undergoes 1α-hydroxylation to form more active 1,25 dihydroxyvitamin D, and granuloma cells possess high amounts of 25-hydroxyvitamin D-1α-hydroxylase, responsible for this conversion (Bell et al, 1979). Elevated serum calcium concentrations may be found in about 11% of patients with sarcoidosis, abnormal urinary calcium loss in about 40 % of patients, and nephrocalcinosis in about 10 % [Ianuzzi et al, 2007].…”
Section: Altered Calcium Metabolismmentioning
confidence: 99%